The Persistence of de Facto Power: Elites and Economic Development in the US South, 1840-1960 - Philipp Ager (European Historical Economics Society (EHES), 2013)
Wealthy elites may end up retarding economic development for their own interests. This paper examines how the historical planter elite of the Southern US affected economic development at the county level between 1840 and 1960. To capture the planter elite's potential to exercise de facto power, I construct a new dataset on the personal wealth of the richest Southern planters before the American Civil War. I find that counties with a relatively wealthier planter elite before the Civil War performed significantly worse in the post-war decades and even after World War II. I argue that this is the likely consequence of the planter elite's lack of support for mass schooling. My results suggest that when during Reconstruction the US government abolished slavery and enfranchised the freedmen, the planter elite used their de facto power to maintain their influence over the political system and preserve a plantation economy based on low-skilled labor. In fact, I find that the planter elite was better able to sustain land prices and the production of plantation crops during Reconstruction in counties where they had more de facto power.
Keywords: 330; Long-Run Economic Development; Wealth Inequality; Elites and Development; de Facto and de Jure Power; US South